PENGGUNAAN PERMAINAN EDUKASI UNTUK MENINGKATKAN MINAT BELAJAR MATEMATIKA DI SD HARAPAN NIAS - Foahonoa Zisokhi Nehe (Haga : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity aims to enhance students’ interest in learning mathematics at SD Harapan Nias through the application of educational games. The methods used include needs identification, teacher training, and the implementation of games in learning. The results of the service indicate a significant increase in students’ interest and understanding of mathematics, with over 80% of students reporting a more enjoyable learning experience. Additionally, social interaction and teamwork skills among students also improved. Positive feedback from teachers reinforces the effectiveness of this method. This service recommends the integration of educational games into the curriculum to improve the quality of education in the school.